2017
DOI: 10.1051/matecconf/201710608056
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of the rational worker incentive system

Abstract: Abstract.The article presents a model of rational incentive system with the structure consisting of three blocks. The first block (financial incentives) provides monetary compensation to a worker. The second block (stimulating by comfortable living conditions) is aimed to regulate the quality of a worker's life in and outside the place he works. The third block (non-financial incentives) takes into account cultural and social worker's needs. The proposed structure of incentive system provides the most comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…So, the first Criminal Code of the RSFSR of 1922 included a section called "other measures of social protection" including rules on placement in institutions for the mentally or morally defective; compulsory treatment; the prohibition to hold a particular position or engage in a particular activity or craft; removal from a specific area. Relative to minors between the ages of 14 and 16, measures of medical and pedagogical impact were envisaged [17]. It is obvious that legislator thus eliminated the line between the two independent institutes of penal actions, defining punishment and other measures of social protection as the main, only and whole means of crime.…”
Section: Discussionmentioning
confidence: 99%
“…So, the first Criminal Code of the RSFSR of 1922 included a section called "other measures of social protection" including rules on placement in institutions for the mentally or morally defective; compulsory treatment; the prohibition to hold a particular position or engage in a particular activity or craft; removal from a specific area. Relative to minors between the ages of 14 and 16, measures of medical and pedagogical impact were envisaged [17]. It is obvious that legislator thus eliminated the line between the two independent institutes of penal actions, defining punishment and other measures of social protection as the main, only and whole means of crime.…”
Section: Discussionmentioning
confidence: 99%
“…This situation is often used by investors and developers who plan to erect objects of spot development: if the boundaries of the land plot are not indicated in the cadastral registration system, then, if necessary, the court decision can accelerate the procedure of surveying with neighboring houses, which leads to an additional problem of corruption of the executive bodies. On the basis of the foregoing, it can be concluded that infill development is inherently contrary to the idea of creating favorable living conditions for citizens and maintaining an ecologically normal habitat [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…1). [4,6,7] An important feature of a rational incentive system is that it makes possible selfdetermination by the organizations (according to the needs of workers as well as their own capabilities, available resources and the existing limitations) of the structure of their incentive system [8]. The proposed model provides a choice (like the menu in the cafeteria) by the organization needed and possible (rational for it) components of the incentive system.…”
Section: мEthodologymentioning
confidence: 99%